2022
DOI: 10.1097/as9.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Marital Status Following Roux-en-Y Gastric Bypass and Sleeve Gastrectomy: A US Multicenter Prospective Cohort Study

Abstract: Among a US cohort followed 5 years after Roux-en-Y gastric bypass or sleeve gastrectomy, cumulative incidence of marriage and separation/divorce were 18% among unmarried (N=614) and 13% among married (N=827) participants, respectively. Preoperative predictors of marriage included younger age, college degree, lower BMI and cohabitating or being separated (versus single). Objectives: To describe changes in marital status following Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Similar responses in the brain are triggered by alcohol, drugs, and food [12] . This aligns with the theory of 'addiction transfer' that suggests patients cannot fulfill the behavior of eating and experience its reward as they did before surgery, so it is replaced with a new behavior that achieves a similar reward, like drinking alcohol [12,182] . Patients can also have an increase in sensitivity to the hormone ghrelin after surgery, which may increase the rewarding properties of alcohol quicker and more frequently [12] .…”
Section: Alcohol Dependencysupporting
confidence: 69%
See 1 more Smart Citation
“…Similar responses in the brain are triggered by alcohol, drugs, and food [12] . This aligns with the theory of 'addiction transfer' that suggests patients cannot fulfill the behavior of eating and experience its reward as they did before surgery, so it is replaced with a new behavior that achieves a similar reward, like drinking alcohol [12,182] . Patients can also have an increase in sensitivity to the hormone ghrelin after surgery, which may increase the rewarding properties of alcohol quicker and more frequently [12] .…”
Section: Alcohol Dependencysupporting
confidence: 69%
“…Patients with RYGB are seen to have a decrease in dopamine D2 receptor availability, specifically in the ventral striatum and caudate nucleus, which are areas of the brain that play an important role in regulating the body's alcohol reward system [12] . Some individuals may be genetically predisposed to reduced dopamine signaling in the alcohol reward system [12,182] . Additionally, psychosocial factors such as depression, anxiety, smoking, and other substance abuse disorders may increase the likelihood of developing alcohol dependence in postoperative bariatric patients [12] .…”
Section: Alcohol Dependencymentioning
confidence: 99%
“…Sexual orientation and gender identity could influence relationship functioning, body image, and weight loss (Hecht et al, 2019), which may limit the generalizability of the results. Romantic relationship status was assessed at presurgical evaluation only; relationship status may have changed after the presurgical evaluation (King et al, 2022). Finally, the study did not assess relationship quality, which limits the ability to discuss the day-to-day lived experience of these relationships as they relate to patients' weight.…”
Section: Limitationsmentioning
confidence: 99%
“…These studies were older, rarely examined outcomes beyond 1-year postsurgery, and were limited to samples that assessed marital rather than romantic relationship status, meaning they may misclassify those in significant but not married relationships. More recently, a study found that among those who were married prior to surgery, there was a 1.40–1.66 incidence rate ratio of divorce 5-year postsurgery (King et al, 2022), suggesting that shifts may be occurring with the family system that leads to real-world changes for patients. Furthermore, Wedin et al (2014) found that being partnered at baseline was associated with greater odds of experiencing successful weight loss 2 years after bariatric surgery.…”
mentioning
confidence: 99%